Viral Lobbying - Crepaz, Michele; Junk, Wiebke Marie; Hanegraaff, Marcel; Berkhout, Joost (2022)
Pandemic policies have been the focus of fierce lobbying competition by different social and economic interests. The contributions in this book analyse patterns in and implications of this ‘viral lobbying’. Based on surveys and focus group interviews, the book provides novel evidence on the lobbying strategies used during the pandemic, as well as the resulting access to and lobbying influence on public policy.